Practical pursuits : Takano Chōei, Takahashi Keisaku, and western medicine in nineteenth-century Japan - Nakamura, Ellen Gardner, 1971- (Harvard East Asian monographs, 2005)
"The history of Western medicine in the late Tokugawa period is usually depicted as a prelude to modern medicine. By comparison to the Western medical science that was systematically introduced in the Meiji period, the Tokugawa study of Western learning is often seen as a hopelessly backward exercise in which inadequately equipped Japanese doctors valiantly struggled to make sense of outdated Dutch knowledge. In contrast, this book argues that the study of Western medicine was a dynamic activity that brought together doctors from all over the country in efforts to effect social change." "By examining the social impact of Western learning at the level of everyday life rather than simply its impact at the theoretical level, the book offers a broad picture of the way in which Western medicine, and Western knowledge, was absorbed and adapted in Japan."--Jacket